Exercise and respiratory tract viral infections - Martin, S.; Pence, B. D.; Woods, J. A. (Exercise and Sport Sciences Reviews, 2009)
Prolonged intense exercise causes immunosuppression, whereas moderate-intensity exercise improves immune function and potentially reduces risk and severity of respiratory viral infections. Here, based on available evidence, we present a model whereby moderate exercise-induced increases in stress hormones reduce excessive local inflammation and skew the immune response away from a TH1 and toward a TH2 phenotype, thus improving outcomes after respiratory viral infections.